Knowledge, attitude and practice in parents of chronically transfused thalassemic patients regarding thalassemia in thalassemia day care unit in government medical college, Amritsar, Punjab, India - Kalra, Riya Kaur; Kaur, Dania; Sodhi, Manmeet; Kaur, Jasleen (International Journal of Contemporary Pediatrics, 2019)
Background: Thalassemia is a chronic debilitating disease that affects nearly 200 million people worldwide. A caregiver who has good knowledge regarding the disease can not only provide a better quality of care to his/her ward but also may spread knowledge in the society in which he/she lives which helps immensely in raising community awareness related to the disease. Methods: 50 caregivers (either mother or father) of chronically transfused thalassemic children were questioned regarding their knowledge, attitude and practice towards this disease, using a self-constructed questionnaire. Results: It was found that despite adequate knowledge regarding every aspect of this disease, there is a lack of attitude of practice towards prevention of this disease in their subsequent child or in their near and dear ones. Conclusions: There is a need to promote an attitude of practice in prevention of the birth of thalassemic children as mere knowledge regarding the disease is not enough in the present scenario where the disease burden is increasing as is the financial and emotional burden on the families. Role of Government sponsorship, a social worker and a child psychologist in the Thalassemia day care unit cannot be minimized.